PENGARUH BODY CONDITION SCORE TERHADAP RESPON ESTRUS SETELAH SINKRONISASI DENGAN CONTROLED INTERNAL DRUG RELEASE PADA KAMBING PERANAKAN ETTAWA - , GALY HARDYTA ([Yogyakarta] : Universitas Gadjah Mada, 2013)
As the increasing of livestock product demand, is needed technology to improve livestock productivity. One of technology that can be used is a reproductive technology namely Controlled Internal Drug Release (CIDR). In this research, the purpose was to determine the effect of Body Condition Score (BCS), especially BCS 2 and BCS 3, to estrous response of Ettawa Crossbreed (PE) which was synchronized with CIDR. Eight female goats PE were divided into two groups, namely group I with a score of 2 and group II with a score of 3. Estrus synchronization was done by embedding CIDR into the vagina for 12 days. Estrus response was detected every 6 hours for 72 hours after CIDR removed. The response which was observed included vaginal temperature, vulvaâs color, and presence or absence of clear mucus at the vulva. The others data which were taken such as the beginning and duration of estrus. Every data were analyzed with different analysis. Increasing of vaginal temperature were analyzed linear regression, while the onset of estrus and duration of estrus were analyzed using T-test. The measurement results showed that there was an increase in vaginal temperature of group BCS 2 about 0.02 Âº C while in group BCS 3 vaginal temperature was decreased about 0.02 Âº C. Estrous occurred earlier in group BCS 3 after 39 hours, while at the BCS group 2 occurred after 42 hours. Duration of estrus in group 3 BCS last longer that is for 28.5 hours while in the BCS group 2 occurs only for 27 hours. Statistical analysis showed that the beginning and duration of estrus in both BCS was not significantly different. The conclusion is mounting CIDR for 12 days can be done to synchronize estrus in goats with BCS 2 and BCS 3 and produces the same amount of estrus response is 100%.